Pengaruh Good Corporate Governance dan Financial Indicators terhadap Financial Distress pada Perusahaan Property dan Real Estate - Retno Mulansari; Wahyu Setiyorini (University of Merdeka Malang, 2019)
The purpose of this study was to examine and research the effect of Good Corporate Governance and Financial Indicators to Financial Distress.Good Corporate Governance was measured by using the institutional ownership, managerial ownership, director size, and independent board of commissioners. Financial Indicators was measured by using liquidity, profitabilty, and leverage. While the indicator financial distress was using Altman Z”-Score Model. The research method used is hypothesis testing research using multiple linear regression tests. Population of this research are all of property real estate sector listed in Indonesia Stock Exchange in the period of 2013-2017. Based on predetermined criteria, the samples obtained were 20 companies. The result of this research showed that institutional ownership, managerial ownership, liquidity, and profitability have significant positive impact on the probability of firm experienced financial distressed and leverage have significant negative impact on the probability of firm experienced financial distressed. While the director size and independent board of commissioners do not affect on the probability of firm experienced financial distressed.